Study on the application of prone and supine lung recruitment maneuvers in the treatment of atelectasis after minimally invasive direct coronary artery bypass surgery - Xin, Yue; Meng, Zelin; Fu, Zhou; Su, Pixiong (Frontiers in Surgery, 2025)
BackgroundAtelectasis is a common complication after minimally invasive direct coronary artery bypass grafting (MIDCABG), which can lead to hypoxemia and even life-threatening conditions. This study aimed to compare the efficacy of prone vs. supine lung recruitment maneuvers in patients undergoing MIDCABG.MethodsThis retrospective study included 170 patients who underwent MIDCABG and developed hypoxemia due to atelectasis during postoperative invasive mechanical ventilation in the cardiac surgical intensive care unit (CSICU). Patients were randomized into prone and supine groups. Clinical recovery indicators and physiological and laboratory parameters at different time points were compared between the two groups. Multiple linear regression was used to analyze the effect of different lung recruitment strategies on the improvement of the oxygenation index. Subgroup analyses were conducted to assess whether the effect of prone vs. supine lung recruitment on oxygenation improvement varied across different patient populations.ResultsProne-position lung recruitment significantly reduced hospital stay, extubation time, time to first ambulation, time to first flatus, duration of mechanical ventilation, and duration of non-invasive oxygen therapy. Lung recruitment strategies significantly improved oxygenation index, carbon dioxide elimination, heart rate control, and inflammatory markers, with the prone group showing superiority at multiple key time points. Multiple linear regression indicated that the prone lung recruitment strategy significantly enhanced the improvement of the oxygenation index, and this effect remained robust after adjusting for age, sex, BMI, and baseline comorbidities. Subgroup analyses revealed that the beneficial effect of prone lung recruitment was more pronounced in patients without diabetes and those with a history of PCI.ConclusionLung recruitment significantly improves oxygenation, carbon dioxide clearance, heart rate control, and inflammatory markers in MIDCABG patients with postoperative atelectasis, with the prone strategy being more effective than the supine. Multivariable and subgroup analyses confirmed the robustness of this effect, particularly in non-diabetic patients and those with a history of PCI.